Unraveling the Black Box of Prison Visitation: Incarcerated Individuals’ and Visitors’ Conversations and Feelings During Visitation Hour - de Jong, Ellen W. A. (Crime & delinquency, 2024)
The nature of prison visits is likely to explain differences in visitation effects, but has received little research attention. Unique survey data of the Dutch Prison Visitation Study enable us to provide a first systematic account of the nature of visits, by describing the topics of conversation and experienced feelings of both incarcerated individuals (n = 787) and visitors (n = 662). Results indicate much variation in feelings (positive and negative) and topics of conversation (emotional and problem-solving topics), a strong link between topics and feelings, and show that visitors have more negative visitation experiences than incarcerated individuals. These insights into the nature of visits help to uncover the black box of prison visitation and provide directions for future research.